Use of a Rubric to Improve the Quality of Internal Medicine Resident Event Reporting - Monica Arnell; Rosemary Demet; Lindsay Vaclavik; Xiaofan Huang; Kristen A. Staggers; Cecilia Y. Cai; Molly J. Horstman (Association of American Medical Colleges, 2021)
Introduction As frontline providers, residents report patient safety events and provide crucial safety feedback. Specific ACGME and AAMC requirements for graduating residents include active participation in event reporting and patient safety investigations. However, formal training on what information a quality event report should include to effect real change in the health care system is lacking. Methods This practical, interactive, case-based workshop educates residents on the key components of a quality event report in a 1-hour time frame. The scoring rubric offers quantitative feedback on the quality of information provided in residents' own event reports. The materials include a presentation template, sample teaching points, pre- and posttraining patient safety cases for residents to complete their own event reports about, and a standardized rubric to score event reports for feedback. Results During the fall of 2019, 198 internal medicine residents completed the workshop, and 143 matched pre- and postcourse surveys were reviewed. Residents' ability to correctly identify the key concepts of an event report improved from a median score of 4 to 8 (p < .001). After completion of training, residents reported increased knowledge regarding the content of an effective event report (p < .001) and increased confidence in their ability to write one (p < .001). Discussion Residents' knowledge of key event-reporting concepts and confidence in reporting improved after completion of the workshop. This brief interactive training and its novel rubric can be used as a standardized tool for patient safety curricula in academic training programs.